2022
DOI: 10.1007/s11145-022-10327-w
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of reading text comprehension from paper and screen in first graders: a longitudinal study

Abstract: Research on text comprehension in relation to the reading medium (paper or screen) has mainly involved undergraduate or high school students. To advance current knowledge on the effects of reading medium, this longitudinal study focused on beginner readers, specifically, the role of precursors in first graders’ comprehension of narrative and expository linear texts from reading on paper and computer screen. Working memory and inference skills as cognitive precursors and basic digital skills were measured at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…There is no significant relationship between other sub-dimensions and general scores. In the literature, there are studies that have obtained results that digital reading affects reading comprehension (Al Khazaleh, 2021;Florit, et al,2022;) as well as studies that do not support reading comprehension (Goodwin, et al, 2020;Støle et al, 2020). Factors such as readers' familiarity with reading in digital environment, the type of device and environment in which digital reading is performed may affect the direction of the relationship between digital reading motivation and comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant relationship between other sub-dimensions and general scores. In the literature, there are studies that have obtained results that digital reading affects reading comprehension (Al Khazaleh, 2021;Florit, et al,2022;) as well as studies that do not support reading comprehension (Goodwin, et al, 2020;Støle et al, 2020). Factors such as readers' familiarity with reading in digital environment, the type of device and environment in which digital reading is performed may affect the direction of the relationship between digital reading motivation and comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only three of the 27 studies have measured reading comprehension using digital devices (Brevik & Hellekjaer, 2018;Brevik et al, 2016;Yeom & Jun, 2020). Several meta-analyses have shown the superiority of paper over digital media in terms of reading comprehension, especially when the texts are expository (Clinton, 2019;Delgado et al, 2018;Florit et al, 2022). However, there is an under-representation of studies specifically looking at the impact of the medium on the reading comprehension of learners of English as a second language.…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, many of these reading tasks in the academic context involve the use of digital devices. There is evidence about the interactive effect of reading medium and text genre on reading comprehension (Florit et al, 2022). Recent metaanalyses have found that reading comprehension can be affected by the medium of presentation of texts.…”
Section: Introductionmentioning
confidence: 99%
“…Confrontando infatti bambini con bassi e bambini con alti livelli di comprensione, emergono due differenti pattern: i primi beneficiano del digitale ed i secondi ottengono punteggi più alti nella modalità cartacea. Questo risultato potrebbe essere in parte legato a fattori motivazionali: bambini con difficoltà di comprensione potrebbero ottenere performance maggiori al computer rispetto che su carta grazie all'alta motivazione che caratterizzata il digitale rispetto al cartaceo (Golan, Barzillai, e Katzir 2018;Florit et al 2022). Dall'altro lato, il vantaggio del digitale sul cartaceo nei bambini con difficoltà di comprensione potrebbe essere legato all'elaborazione superficiale, tipica del digitale (Annisette e Lafreniere 2017), che favorisce prestazioni migliori in domande semplici di natura testuale che caratterizzano i brani di comprensione del testo in età precoce.…”
Section: Risultatiunclassified